(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to study the proposed A program to audit compliance with the application of the IAS No. 26 ( accounting and reporting on retirement benefit plans) adapted to the law of salaries of state and public sector employees No. 22 of 2008 "amended" and the unified Retirement Law No. 9 of 2014 "amended" In accordance with the unified accounting system in the State Employees’ Pension Fund in Baghdad, and the importance of the research lies in light of its presentation of the intellectual, knowledge and applied contributions to audit procedures through the proposed audit program and represented the research community of pension funds located in Iraq represented by the research sample ( State Employees’ Pension Fund in Baghdad ) and the research problem was the lack of a program to audit compliance with this application in the State Employees Pension Fund in the State Employees’ Pension Fund and the research was based on the standard international accountant No. 26 ( accounting and reporting on retirement benefit plans) and audit program of the State Employees Pension Fund currently applied by the Financial Control Authority operating in the State Employees Pension Fund in Baghdad The most important conclusions reached by the research is the absence of an audit program to audit compliance with the application of the IAS No. 26 ( accounting and reporting on retirement benefit plans) adapted to the law of salaries of state and public sector employees No. 22 of 2008 "amended" and the unified Retirement Law No. 9 of 2014 "amended" In accordance with the unified accounting system in the State Employees’ Pension Fund in Baghdad and that the main recommendation of this research is the recommendation to the Federal Financial Control Bureau By approving the audit program proposed by the two researchers to audit compliance with the application of the IAS No. 26 ( accounting and reporting on Pension Benefit Plans) adapted to the law of salaries of state and public sector employees No. 22 of 2008 "amended" and the unified Retirement Law No. 9 of 2014 "amended" In accordance with the unified accounting system in the State Employees’ Pension Fund in Baghdad.